Catalytic Dearomative Spirocyclization via Gold Carbene Species Derived from Ynamides: Efficient Synthesis of 2‐Azaspiro[4.5]decan‐3‐ones. Issue 15 (19th February 2018) - Ito, Mamoru; Kawasaki, Ryosuke; Kanyiva, Kyalo Stephen; Shibata, Takanori
Abstract: An intramolecular catalytic dearomatization of phenols via gold carbene species proceeded to provide 2‐azaspiro[4.5]decan‐3‐ones. The use of NHC ligand and water as a co‐solvent was critical for achieving high reactivity. This reaction did not require hazardous diazo compounds as carbene sources and proceeded even under air. The obtained spirocyclic product could be readily transformed into a gabapentin derivative by hydrogenation and deprotection. Abstract : Gold prize for safety : An intramolecular catalytic dearomatization of phenols via gold carbene species proceeded to provide 2‐azaspiro[4.5]decan‐3‐ones. The use of NHC ligand and water as a co‐solvent was critical for achieving high reactivity. This reaction did not require hazardous diazo compounds as carbene sources and proceeded even under air.